Factors influencing the use of epidural labor analgesia: a cross-sectional survey analysis - Li, Wei; Wu, Na; Zhou, Shuangqiong; Du, Weijia; Xu, Zhendong; Liu, Zhiqiang (Frontiers in Medicine, 2024)
Introduction: To explore the personal and organizational factors influencing the lack of implementation of epidural labor analgesia (ELA). Methods: This study was conducted at the Shanghai First Maternity and Infant Hospital, School of Medicine, Tongji University, Shanghai, China. A total of 451 women who underwent vaginal delivery without ELA between October 8, 2021 and March 30, 2022, were included. A questionnaire was used to collect the relevant data. We derived and validated without ELA by using binary logistic regression analysis. Results: Of the total 451 included, 355 (78.7%) initially preferred ELA, whereas 96 (21.3%) rejected it directly. Five variables were validated (P<0.05): multiparas, ELA would lead to back pain, experienced ELA in previous delivery, the inner attitude toward labor pain, blood routine and coagulation function not being tested within14 days. The sensitivity and specificity of this model were 96.3% and 69.8%, respectively. Conclusions: The corresponding training should be provided to the medical staff to identify women at high risk factors of rejecting ELA during the prenatal examination process using a questionnaire, then provide them with knowledge regarding ELA, so that ELA can benefit more mothers. Additionally, the existing organizational factor should be addressed in order to efficiently provide ELA service to mothers.